2017
DOI: 10.1186/s40635-017-0141-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous dialysis on blood pH in acidemic hypercapnic animals with severe acute kidney injury: a randomized experimental study comparing high vs. low bicarbonate affluent

Abstract: Background: Controlling blood pH during acute ventilatory failure and hypercapnia in individuals suffering from severe acute kidney injury (AKI) and undergoing continuous renal replacement therapy (CRRT) is of paramount importance in critical care settings. In this situation, the optimal concentration of sodium bicarbonate in the dialysate is still an unsolved question in critical care since high concentrations may worsen carbon dioxide levels and low concentrations may not be as effective in controlling pH. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 34 publications
0
12
0
3
Order By: Relevance
“…Again, the use of CVVH brings an interesting advantage to resolve this problem. It has been clearly shown that administering intravenous bicarbonate while increasing pH also increases PCO 2 [35], which is the opposite of the expected effect of ECCO 2 R. Other authors have shown that the administration of bicarbonate via a CVVH machine is not accompanied by a concomitant rise in PCO 2 [36, 37] (Fig. 5).…”
Section: Impact Of the Buffermentioning
confidence: 98%
See 1 more Smart Citation
“…Again, the use of CVVH brings an interesting advantage to resolve this problem. It has been clearly shown that administering intravenous bicarbonate while increasing pH also increases PCO 2 [35], which is the opposite of the expected effect of ECCO 2 R. Other authors have shown that the administration of bicarbonate via a CVVH machine is not accompanied by a concomitant rise in PCO 2 [36, 37] (Fig. 5).…”
Section: Impact Of the Buffermentioning
confidence: 98%
“…According to the theory of Stewart, the pH has 3 main determinants: PaCO 2 , strong ion difference (SID), and the presence of weak acid. Romano et al [36] compared blood pH of pigs hemodialyzed with either 20 mEq/L (“group 20”) or 40 mEq/L (“group 40”) of bicarbonate in the dialysate. They postulated that the improved control of blood pH in the animals in group 40 was achieved by higher SID values, due to lower chloride infusion in this group without elevation of PCO 2 .…”
Section: Impact Of the Buffermentioning
confidence: 99%
“…severe metabolic acidosis, and severe respiratory acidosis, is scarce. Currently, large animal models accurately and faithfully replicate severe pathophysiological states and the critical care interventions entailed therein, encompassing many syndromes [2][3][4][5][6][7][8][9][10][11][12], as well as CRRT use [6]. Experimental CRRT brings us the possibility to study renal support in those unusual clinical scenarios [6].…”
mentioning
confidence: 99%
“…In an ongoing experimental line of research, we are investigating the impact of high bicarbonate concentrations on blood pH during continuous venous-venous hemodialysis (CVVHD) in hypercapnic pigs with severe renal failure induced by hilum ligation. ( 1 ) In this described experiment, a female 31kg Landrace pig was used as the research subject. After anesthesia, a central venous line, venous dialysis catheter (12-French, 16cm, Arrow TM , PA, USA), Swan-Ganz catheter (Edwards Lifesciences TM , Irvine, USA), and an arterial line were inserted.…”
mentioning
confidence: 99%
“…In the first experiments, CVVHD was performed using the Fresenius F8® (Fresenius Medical Care TM , MA, USA) low-flow filter without the occurrence of any adverse events or complications. ( 1 ) Due to a shortage of this filter in the Brazilian market, we changed to an Elisio-H17® filter (Nipro Medical LTDA TM , Sorocaba, São Paulo, Brazil). Surprisingly, in the first experiment using the new filter, fatal refractory shock, low cardiac output, and hemoconcentration occurred soon after continuous renal replacement therapy initiation.…”
mentioning
confidence: 99%